Tantangan dan Strategi Biro Pemberitaan Parlemen dalam Menjaga Citra DPR RI Selama Peralihan Pemerintahan - Ferdinand, Rio; Rusdi, Farid (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study aims to examine the editorial strategies employed by the DPR RI Parliamentary News Bureau in maintaining and enhancing the image of the DPR RI during the period of governmental transition. The study adopts a qualitative approach with a descriptive method. Data were collected through in-depth interviews with editors and reporters, as well as observations of the DPR RI’s official social media platforms. The findings indicate that the Parliamentary News Bureau applies Agenda Setting Theory and Propaganda Theory to guide and shape public opinion through news content that emphasizes strategic issues and the positive achievements of the DPR RI. Social media platforms, particularly Instagram and TikTok, serve as the primary channels for information dissemination, complemented by collaborations with external media to broaden audience reach. The study also identifies key challenges, notably the spread of fake news and misinformation, which are addressed through the rapid and neutral delivery of information. The evaluation of editorial performance is conducted routinely through satisfaction surveys, analysis of public engagement on social media, and the timeliness of news dissemination. Overall, this study offers insights that may be valuable for other government institutions in developing effective news strategies and managing institutional image. Penelitian ini bertujuan untuk mengkaji strategi redaksi yang digunakan oleh Biro Pemberitaan Parlemen DPR RI dalam menjaga dan meningkatkan citra DPR RI selama masa pergantian pemerintahan. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data dilakukan melalui wawancara mendalam dengan redaktur dan reporter, serta observasi terhadap media sosial resmi DPR RI. Hasil penelitian menunjukkan bahwa Biro Pemberitaan Parlemen memanfaatkan teori Agenda Setting dan teori Propaganda untuk mengarahkan serta membentuk opini publik melalui pemberitaan yang berfokus pada isu-isu strategis dan capaian positif DPR RI. Media sosial, seperti Instagram dan TikTok, menjadi platform utama dalam penyebaran informasi, yang didukung oleh kerja sama dengan media eksternal untuk memperluas jangkauan. Penelitian ini juga menyoroti tantangan utama berupa berita bohong dan misinformasi, yang diatasi melalui penyampaian informasi secara cepat dan netral. Evaluasi keberhasilan dilakukan secara rutin melalui survei kepuasan, analisis keterlibatan masyarakat di media sosial, serta kecepatan penayangan berita. Penelitian ini memberikan wawasan bagi instansi pemerintahan lain dalam mengembangkan strategi pemberitaan dan manajemen citra.